Exploring the Impact of Perceived Justice and Complaint Handling Satisfaction on Trust and Commitment in Indonesia's E-commerce Fashion Sector - Trisna Intan Sari; Hartoyo Hartoyo; Istiqlaliyah Muflikhati (Journal of Consumer Sciences, 2025)
Background: Indonesia's rapid growth in the e-commerce fashion sector presents opportunities and challenges, particularly in addressing consumer dissatisfaction during post-purchase experiences. Key challenges include product misrepresentation, delivery delays, or unmet expectations, which can lead to negative behaviors such as complaints, reduced loyalty, and distrust toward sellers. Purpose: This study investigates the impact of perceived justice dimensions—interactional, procedural, and distributive—on satisfaction with complaint handling and its subsequent effects on customer trust, customer commitment, and customer loyalty. Methods: This study employed a cross-sectional survey with a purposive sampling technique, collecting data from 174 respondents in the Jabodetabek region. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used for analysis. Findings: This research reveals that distributive and procedural justice significantly influence complaint handling, while interactional justice has a smaller yet notable impact. Complaint handling, in turn, significantly enhances both customer commitment and customer trust, with customer commitment emerging as a stronger driver of customer loyalty. Notably, customer trust's direct effect on customer loyalty is insignificant, suggesting that emotional engagement through commitment plays a more pivotal role in fostering loyalty. Conclusion: These findings underscore the importance of fair complaint resolutions, efficient processes, and empathetic communication in maintaining customer relationships. Research implication: The findings provide actionable insights for e-commerce businesses to improve customer satisfaction with complaint handling, particularly emphasizing the critical roles of distributive justice and procedural justice in fostering satisfaction.